Menstrual cup: awareness among reproductive women - K., Shwetha Ballal; Bhandary, Amritha (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Background: Menstrual cup is an alternative to sanitary pads, which has received attention in relatively small-scale studies in high income, and low- and middle-income countries, including among schoolgirls. Made of high-grade medical grade silicone (biodegradable) have the advantage of reuse, and can potentially last up to 10 years. Objective of this study was to assess and analyse the awareness regarding menstrual cup among the women of reproductive age group. Methods: Data collected from the selected eligible participants by an interviewer administered study proforma. It is a descriptive cross-sectional study over 1 month in women in reproductive age in A. J. Institute Mangalore, Karnataka, India. Results: A total 82% were aware about menstrual cup but only 2.6% have used it. Conclusions: One challenge of menstruation that is taken for granted in affluent countries is the simple question of how to manage or contain the menstrual flow and what happens to a girl or woman who is not able to do this successfully. Menstrual hygiene management is therefore an increasingly important (yet often unrecognized) issue that is heavily intertwined with girls’ education, empowerment, and social development.